Combined Bone Transportation and Lengthening Techniques for the Treatment of Septic Nonunion of the Forearm Followed by Tendon Transfer - Konstantinos Ditsios; Eirini Iosifidou; Lazaros Kostretzis; Panagiotis Konstantinou; Iosafat Pinto; Ioannis Theodoroudis; Ippokratis Hatzokos (Case Reports in Orthopedics)
Infected nonunion of a forearm fracture complicated by a considerable skin-muscle defect poses a great challenge to orthopaedic surgeons. The treatment strategy comprises eradication of the infection, ensuring bony union and soft tissue coverage along with functional restoration. We report a case of a 23-year-old man with an open Gustilo-Anderson IIIb fracture complicated by infected nonunion after internal fixation. After thorough surgical debridement, a considerable soft tissue defect, extensor muscle loss, and posterior interosseous nerve laceration had to be addressed. He was finally treated with bone transportation and bone lengthening followed by tendon transfers.